2019
DOI: 10.1016/j.jmps.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

A fully equilibrated microsphere model with damage for rubberlike materials

Abstract: A non-affine microsphere model for rubberlike materials is proposed, based on a local minimization of the network free energy under a maximal advance path constraint. It accounts for any chain weight distribution and for damage such as Mullins softening observed in filled rubber materials. The non-affine equal-force model is compared to the common affine model and a hybrid equal-force model from the literature, when considering the isotropic hyperelastic behavior without damage of rubber materials presenting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Relaxing some of these assumptions is expected to yield better fittings for the experimental comparisons presented in this work. In particular, the Mullins-like effect observed in Figure b that was not captured by this model has been explained by other researchers by network alteration (reflecting the changes of non-affine deformation) as well as nonlinear viscoelasticity …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Relaxing some of these assumptions is expected to yield better fittings for the experimental comparisons presented in this work. In particular, the Mullins-like effect observed in Figure b that was not captured by this model has been explained by other researchers by network alteration (reflecting the changes of non-affine deformation) as well as nonlinear viscoelasticity …”
Section: Discussionmentioning
confidence: 74%
“…We emphasize the intention of this work to provide a qualitative understanding of the governing physics outlined in Section and note that a more sophisticated numerical strategy could mitigate this. For instance, reducing the model to the domain of a microsphere ,, could significantly reduce computational cost and open the possibility for implementation in finite element method models. We finally note that our usage of a first-order kinetic law, with constant rates of k a and k d , does not account for the force sensitivity of bond lifetime in many physical systems .…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that higher ν would lead to smaller Δ r , which could be ascribed to increased chemically crosslinked network; higher molecular weight polymer network provided more extra reversible deformation, thus there would be less energy dissipation. Zhong et al [ 49 , 50 ] proposed that increasing the elastomer crosslinking degree would result in chain entanglement, slippage, and twisting more likely to occur, therefore leading to the magnitude of strain energy change. However, this strain energy change would also be averaged over the different strains.…”
Section: Resultsmentioning
confidence: 99%
“…To develop a model that accounts for the collective impact delocalized chain rupture events play on the bulk material response, and more specifically on the fracture energy, several key building blocks are needed. Incorporating a chain length distribution to reflect the structural heterogeneity of non-uniform chain length in an elastomer network is a vital starting point that has already been proven to impact elastomer mechanics and fracture (Dargazany and Itskov, 2009;Diani and Le Tallec, 2019;Falender et al, 1979;Guo and Zaïri, 2021;Itskov and Knyazeva, 2016;Lavoie et al, 2019;Li and Bouklas, 2020;Lu et al, 2020;Mark, 2003;Wang et al, 2015;Xiao et al, 2021). Incorporation of chain length polydispersity into the network requires defining the chain-level load sharing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of chain length polydispersity into the network requires defining the chain-level load sharing behavior. The equal strain assumption is commonly employed, where all chains, independent of initial length, are assumed to be deformed to the same stretch (Diani and Le Tallec, 2019;Itskov and Knyazeva, 2016;Tehrani and Sarvestani, 2017). The equal force assumption may also be implemented, where all chains are assumed to bear the same force (via a virtual series arrangement of chains with respect to the loading mechanism) (Li and Bouklas, 2020;Verron and Gros, 2017).…”
Section: Introductionmentioning
confidence: 99%